2006
DOI: 10.1158/1535-7163.mct-05-0420
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid targets in cancer therapy

Abstract: Considerable progress has been made recently in our understanding of the role of ceramide in the induction of apoptotic cell death. Ceramide is produced by cancer cells in response to exposure to radiation and most chemotherapeutics and is an intracellular second messenger that activates enzymes, leading to apoptosis. Because of its central role in apoptosis, pharmacologic manipulation of intracellular ceramide levels should result in attenuation or enhancement of drug resistance. This may be achieved through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 67 publications
1
93
0
1
Order By: Relevance
“…This proapoptotic SL is produced by cancer cells in response to exposure to ionizing radiation and most chemotherapeutic agents, however, some chemo-and radioresistant tumor cells exhibit defects in ceramide generation supporting the emerging role of ceramide as a tumor suppressor lipid [3,4]. Strategies that target the enzymes of ceramide clearance (SMS, GCS or ceramidases), resulting in enhanced ceramide levels in cancer cells, have been developed as novel approaches for anticancer chemotherapy.…”
Section: Page 17 Of 43mentioning
confidence: 99%
See 1 more Smart Citation
“…This proapoptotic SL is produced by cancer cells in response to exposure to ionizing radiation and most chemotherapeutic agents, however, some chemo-and radioresistant tumor cells exhibit defects in ceramide generation supporting the emerging role of ceramide as a tumor suppressor lipid [3,4]. Strategies that target the enzymes of ceramide clearance (SMS, GCS or ceramidases), resulting in enhanced ceramide levels in cancer cells, have been developed as novel approaches for anticancer chemotherapy.…”
Section: Page 17 Of 43mentioning
confidence: 99%
“…Manipulation of cellular sphingolipid (SL) metabolism has been proposed as a means to amplify or restore apoptosis [3]. Indeed, numerous studies have shown that increased intracellular levels of the SL metabolite ceramide inhibit cell proliferation and promote apoptosis of tumor cells (reviewed in [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Ceramide mediates a wide array of stress signals such as anticancer treatments leading to apoptosis, whereas S1P exerts prosurvival capabilities by antagonizing ceramide effects (Modrak et al, 2006). So a ceramide/S1P rheostat has been hypothesized to determine the fate of cell, such that the relative cellular concentrations of ceramide and S1P determine whether a cell proliferates or undergoes apoptosis (Andrieu-Abadie and Levade, 2002;Reynolds et al, 2004;Bieberich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…GCS catalyzes the first step in the biosynthesis of glycosphingolipids, and its cellular activity modulates the levels of the other lipids as well as ceramide (7)(8)(9). Early studies demonstrated that increasing the capacity for ceramide glycosylation in GCS-transfected human breast cancer MCF-7 cells conferred greater resistance to doxorubicin and to TNF-· (10,11).…”
Section: Introductionmentioning
confidence: 99%